2017
DOI: 10.1016/j.jtusci.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different geometric configurations and materials for neutron radiography purposes based on a 241Am/Be neutron source

Abstract: The present work examines two different geometric configurations and three different lining materials that are suitable for thermal neutron radiography purposes based on a 241 Am/Be neutron source. The same source was also used for fast neutron radiography. Appropriate collimators were simulated for each of the radiography modes, comparing the effectiveness of Cadmium, Gadolinium, and Boral as lining materials for thermal neutron radiography and evaluating the efficiency of Iron and Tungsten as interior wall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The material of the collimator is a very important part of the unit and must stop scattered neutrons to reach at the investigated object position. A previous work from Fantidis [44] has shown that boral offers better performance than cadmium or gadolinium. The filling materials must stop both neutrons and gamma so a combination of borated polyethylene (PE-B) and bismuth is a good choice.…”
Section: Thermal Neutron Collimatormentioning
confidence: 98%
See 1 more Smart Citation
“…The material of the collimator is a very important part of the unit and must stop scattered neutrons to reach at the investigated object position. A previous work from Fantidis [44] has shown that boral offers better performance than cadmium or gadolinium. The filling materials must stop both neutrons and gamma so a combination of borated polyethylene (PE-B) and bismuth is a good choice.…”
Section: Thermal Neutron Collimatormentioning
confidence: 98%
“…In order to overcome the lack of the nuclear reactors, the required neutron beams usually are derived by accelerators or from some isotopic sources. A typical facility includes Deuterium-Tritium (DT) [34], Deuterium-Deuterium (DD) [34]- [37], Tritium-Tritium (TT) [34], [38] neutron generators, 252 Cf [39][40][41], 241 Am/Be [42][43][44] isotopic neutron sources, proton [45] or electron [46] usually on accelerators on beryllium [10], [47][48][49][50] or lithium [51] targets.…”
Section: Introductionmentioning
confidence: 99%